Eat Behavior Muara Goat (Capra aegagrushircus) in the village of Batubinumbun, Muara, North Tapanuli Regency - H H Silitonga; Hamdan; I Sembiring; N Ginting; Hasnudi (Talenta Publisher, 2017)
Goat eating behavior can support nutrition of goat feed. This information is important for farmers in an attempt for Muara condition the environment and design the appropriate management needs goats. This research was conducted in July and August 2016. Livestock were used as many as 30 individuals. Eating behavioral observations performed on four groups, namely: group I (adult males and adult females with a ratio of 1: 9), Group II (adult males and adult females with a ratio of 1: 4), Group III (young male 6 tails and females young or virgin 4 individuals) and group IV (tiller consists of 2 males and females tails 3 tails). Research method was One Zero with a 15 minute interval performed on at 08.00-12.00. The results showed higher feeding activity compared to activity of rumination, the group with the highest feeding activity in the goat group samplings, rumination activity while highest in the group of adult goat.